Impact of daptomycin dose exposure alone or in combination with β-lactams or rifampin against vancomycin-resistant enterococci in an in Vitro biofilm model (2020)
Enterococcus faecium strains are commonly resistant to vancomycin and β-lactams. In addition, E. faecium often causes biofilm-associated infections and these infections are difficult to treat. In this context, we investigated the activity of dosing regimens using daptomycin (DAP) (8, 10, 12, and 14 mg/kg of body weight/ day) alone and in combination with ceftaroline (CPT), ampicillin (AMP), ertapenem (ERT), and rifampin (RIF) against 2 clinical strains of biofilm-producing vancomycinresistant Enterococcus faecium (VREfm), namely, strains S447 and HOU503, in an in vitro biofilm model. HOU503 harbors common LiaS and LiaR substitutions, whereas S447 lacks mutations associated with the LiaFSR pathway. MIC results demonstrated that both strains were susceptible to DAP and resistant to CPT, AMP, ERT, and RIF. The 168-h pharmacokinetic/pharmacodynamic (PK/PD) CDC biofilm reactor models (simulating human antibiotic exposures) were used with titanium and polyurethane coupons to evaluate the efficacy of antibiotic combinations. DAP 12 and 14 achieved bactericidal activity against S447 but lacked such effect against HOU503. Addition of ERT and RIF enhanced DAP activity, allowing DAP 8 and 10 plus ERT or RIF to produce bactericidal activity against both strains at 168 h. While DAP 8 and 10 plus CPT improved killing, they did not reach bactericidal reduction against S447. Combination of AMP, CPT, ERT, or RIF resulted in enhanced and bactericidal activity for DAP against HOU503 at 168 h. Our data provide further support for the use of combinations of DAP with AMP, ERT, CPT, and RIF in infections caused by biofilm producing VREfm. Further research involving DAP combinations against biofilm-producing enterococci is warranted.